The effect of trimethazidine on mortality in an experimental acute pancreatitis model1 - Ergücük, Hakan; Işık, Sevil; İflazoğlu, Nidal; Kayaalp, Cüneyt; Saraç, Mehmet; Gürsul, Serdar (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Acute pancreatitis has a high morbidty and mortality. Its physiopathogenesis has not been enlightened up to the present. This study aims to investigate trimetazidine (antiischemic, antioxidant and cardioprotective agent) ’s effects on the acute pancreatitis.Materials and Methods: In this study, four aqual groups are formed with 43 female Spraque-dawley type rats weighed between230-300 gr (mean 265 gr). 0.9% NaCl is injected intraperitoneally after laparotomy to the Group 1 (n=6). Group 2 (n=6) is control group that without any intervention. Acute pancreatitis is formed in Group 3 (n=16) via injection of Na-taurokolat in the common bile duct. Group 4 (n=15) is being formed pancreatitis and treated with Trimetazidine. In group 4 Trimetazidine 10 mg/kg/day drugs were given, 30 minutes, 24 and 72 hours after formation of acute pancreatitis, in three equal doses by orogastric way. In all groups, the rats have been laparatomised 72 hours later under general anesthesia and pancreas tissues has been extracted and studied histopathologically. Amylase, lipase, lactate dehydrogenase, aspartate transaminase, alanine tranaminase levels in the rats serum and superoxide dismutase, catalase, glutathione, malondialdehyde, nitric oxide, protein carbonyl, glutathione peroxidase levels in the rats tissue also have been looked up.Results: Serum and tissue findings and histopathologically examination of the pancreas tissues show significant decrease in the treatment group compare to study group.Conclusion: Trimetazidine protects pancreas tissue and decreases the mortality by significantly lowering the biochemical and histopathological changes in the early stages of acute pancreatitis.